Solid-liquid composite microcapsule, preparation method and application thereof
By combining lubricant and two-dimensional materials in microcapsules, using specific shell materials and preparation methods, the problem of lubrication failure of traditional microcapsules under high loads is solved, and excellent lubricating performance under large contact area and high loads is achieved.
Patent Information
- Application Number
- CN202310178159.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Traditional microcapsule composite materials are prone to lubrication failure under large contact area and high loads, limiting their application and promotion in mechanical parts.
It adopts solid-liquid composite microcapsules, the core material includes lubricant, two-dimensional material and dispersant, and the shell material is made of urea-formaldehyde resin, polyimide and other materials, and is prepared by in-situ polymerization, interface polymerization and solvent evaporation. The two-dimensional material and lubricant are evenly dispersed to ensure effective lubrication under high loads.
It achieves excellent lubricating performance under large contact area and high load bearing, avoids two-dimensional material precipitation, and improves the friction coefficient and wear performance of microcapsules.
Smart Images

Figure CN116212756B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of self-lubricating materials, and in particular to a solid-liquid composite microcapsule, a preparation method thereof, and an application thereof. Background Art
[0002] Microcapsules are a new type of lubricant filler, and their core-shell structure is formed by encapsulating lubricant materials such as lubricants or phase change materials in an organic shell or an inorganic shell. Microcapsules can be compounded with various polymer matrix materials and significantly reduce the friction coefficient and wear rate of the matrix material. During the friction process, the microcapsules in the matrix will be destroyed by pressure and shear force, and the lubricating material encapsulated inside will be released to form an effective lubricating film at the friction interface to reduce the friction coefficient. In addition, the presence of the lubricating film can prevent direct contact with the rough peaks, avoid the occurrence of material wear, and thus reduce the wear rate of the material.
[0003] However, conventional studies on surface contact testing of microcapsule composites have focused on low loads of 1MPa-3MPa and a contact area of 60mm. 2 In the case of large contact area (greater than 120mm 2 ) and high load (greater than 10MPa), traditional microcapsule composite materials are prone to lubrication failure, which greatly limits their application and promotion in mechanical parts. Summary of the invention
[0004] Based on this, it is necessary to provide a solid-liquid composite microcapsule, a preparation method and application thereof. The solid-liquid composite microcapsule has excellent lubrication performance under a large contact area and high load.
[0005] The first aspect of the present application provides a solid-liquid composite microcapsule, comprising a core material and a shell material coating the core material, wherein the core material comprises a lubricant, a two-dimensional material and a dispersant, and the two-dimensional material comprises one or more of graphene, molybdenum disulfide, tungsten disulfide, boron nitride and black phosphorus.
[0006] In some embodiments, the lubricant includes one or more of polyalphaolefin, perfluoropolyether, silicone oil, and tung oil.
[0007] In some embodiments, the mass ratio of the two-dimensional material to the lubricant is (0.01-0.25):1.
[0008] In some preferred embodiments, the mass ratio of the two-dimensional material to the lubricant is (0.1-0.2):1.
[0009] In some embodiments, the dispersant includes one or more of Tween 80, boronated polyisobutylene bissuccinimide, polyisobutylene succinate, benzylamine, and ashless phosphate.
[0010] In some embodiments, the shell material includes one or more of urea-formaldehyde resin, polyimide, polystyrene, polyurethane and polysulfone.
[0011] In some embodiments, based on the lubricant, the mass percentage of the dispersant to the lubricant is 0.1% to 10%.
[0012] In some embodiments, the mass percentage of the core material in the solid-liquid composite microcapsule is 40% to 60%.
[0013] The second aspect of the present application provides a method for preparing the solid-liquid composite microcapsule described in the first aspect of the present application, wherein the preparation method comprises one or more of an in-situ polymerization method, an interfacial polymerization method and a solvent evaporation method.
[0014] In some embodiments, the in situ polymerization method comprises the following steps:
[0015] Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material;
[0016] The core material is emulsified into micro-oil droplets in an aqueous phase containing a surfactant and a first shell material raw material, and the first shell material raw material is polymerized on the surface of the micro-oil droplets to form the shell material.
[0017] In some specific embodiments, the first shell material raw material includes at least two of urea, formaldehyde, polyisocyanate and unsaturated polyol.
[0018] In some embodiments, the interfacial polymerization method comprises the following steps:
[0019] Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material;
[0020] After the initiator and the core material are mixed, the core material is emulsified into oil droplets in an aqueous phase containing a surfactant and a second shell material raw material, and the second shell material raw material is polymerized under the action of the initiator to form the shell material.
[0021] In some specific embodiments, the initiator includes one or more of azobisisobutyl cyanide, potassium persulfate, benzoyl peroxide and azobisisoheptyl cyanide.
[0022] In some specific embodiments, the second shell material comprises one or more of methyl methacrylate, styrene and methyl styrene.
[0023] In some embodiments, the solvent evaporation method comprises the following steps:
[0024] Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material;
[0025] Dissolving the core material and the third shell material raw material in an organic solvent to obtain a mixed solution;
[0026] dispersing the mixed solution into an aqueous phase containing a surfactant for emulsification;
[0027] The emulsified liquid obtained by emulsification is heated to volatilize the organic solvent, and the third shell material raw material is precipitated to form the shell material, and the shell material covers the core material.
[0028] In some specific embodiments, the organic solvent includes one or more of dichloromethane, dimethylformamide and chloroform.
[0029] In some specific embodiments, the third shell material includes one or more of polyimide, polystyrene, polymethyl methacrylate and polysulfone.
[0030] The third aspect of the present application provides an application of the solid-liquid composite microcapsule described in the first aspect of the present application or the solid-liquid composite microcapsule prepared by the preparation method described in the second aspect of the present application in the preparation of a lubricating material.
[0031] Compared with the conventional technology, the above solid-liquid composite microcapsules, their preparation method and application have at least the following advantages:
[0032] The dispersant in the core material of the solid-liquid composite microcapsule can promote the uniform dispersion of the two-dimensional material in the lubricant, and prevent the two-dimensional material from settling in the lubricant and affecting the lubrication performance of the microcapsule. The shell material of the solid-liquid composite microcapsule encapsulates the lubricant dispersed with the two-dimensional material in the microcapsule, so that the two-dimensional material can be released together with the lubricant when the microcapsule is broken, thereby achieving excellent lubrication performance of the microcapsule under a large contact area and high load. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic structural diagram of a solid-liquid composite microcapsule according to an embodiment of the present application, wherein: 1-shell material; 2-core material.
[0034] Figure 2 This is a scanning electron microscope image of the solid-liquid composite microcapsule prepared in Example 1 of the present application.
[0035] Figure 3 This is a transmission electron micrograph of the solid-liquid composite microcapsules prepared in Example 1 of the present application.
[0036] Figure 4 This is a graph of the friction coefficient of the solid-liquid composite microcapsules prepared in Example 1 of the present application under different loads.
[0037] Figure 5This is a graph of the friction coefficient of the solid-liquid composite microcapsules prepared in Comparative Example 1 of the present application under different loads. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0039] In the description of this application, unless otherwise defined, unspecified professional terms and professional words have the same meaning as those commonly understood by those skilled in the art and are common knowledge of those skilled in the art, and unspecified methods are conventional methods known to those skilled in the art. The term "multiple" in this application means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0040] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0041] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0043] One embodiment of the present application provides a solid-liquid composite microcapsule, including a core material and a shell material coating the core material, the core material includes a lubricant, a two-dimensional material and a dispersant, and the two-dimensional material includes one or more of graphene, molybdenum disulfide, tungsten disulfide, boron nitride and black phosphorus.
[0044] The dispersant in the core material can promote the uniform dispersion of the two-dimensional material in the lubricant, and prevent the two-dimensional material from settling in the lubricant and affecting the lubrication performance of the microcapsule. Two-dimensional materials such as graphene, molybdenum disulfide, tungsten disulfide, boron nitride and black phosphorus have good lubrication performance. The shell material encapsulates the lubricant dispersed with the two-dimensional material in the microcapsule, so that when the microcapsule is broken, the two-dimensional material can be released together with the lubricant, thereby achieving excellent lubrication performance of the microcapsule under a large contact area and high load. The structure of the solid-liquid composite microcapsule of this embodiment is as follows: Figure 1 As shown, the shell material 1 covers the core material 2.
[0045] In some embodiments, the solid-liquid composite microcapsule is a spherical structure.
[0046] In some embodiments, the lubricant includes one or more of polyalphaolefins, perfluoropolyethers, silicone oils, and tung oils.
[0047] In some embodiments, the mass ratio of the two-dimensional material and the lubricant is (0.01-0.25):1. It can be understood that controlling the mass ratio of the two-dimensional material and the lubricant to (0.01-0.25):1 can make the morphology of the solid-liquid composite microcapsule a spherical structure, thereby further improving the lubrication performance of the solid-liquid composite microcapsule. When the mass ratio of the two-dimensional material and the lubricant is too high, the two-dimensional material may be embedded in the shell material, so that the solid-liquid composite microcapsule is in the shape of a rod, dumbbell, ellipse, etc., affecting the lubrication performance of the solid-liquid composite microcapsule; when the mass ratio of the two-dimensional material and the lubricant is too low, the two-dimensional material and the lubricant synergistically improve the lubrication performance of the solid-liquid composite microcapsule. The mass ratio of the two-dimensional material and the lubricant may include, but is not limited to: 0.01:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1 or 0.25:1, etc.
[0048] In some preferred embodiments, the mass ratio of the two-dimensional material to the lubricant is (0.1-0.2): 1. It can be understood that when the mass ratio of the two-dimensional material to the lubricant is (0.1-0.2): 1, the lubrication performance of the solid-liquid composite microcapsule is better.
[0049] In some embodiments, the dispersant includes one or more of Tween 80, boronated polyisobutylene bissuccinimide, polyisobutylene succinate, benzylamine, and ashless phosphate.
[0050] In some embodiments, the shell material includes one or more of urea-formaldehyde resin, polyimide, polystyrene, polyurethane, and polysulfone.
[0051] In some embodiments, the mass percentage of the dispersant to the lubricant is 0.1% to 10% based on the lubricant. It is understood that the mass percentage of the dispersant to the lubricant based on the lubricant may include but is not limited to: 0.1%, 2%, 4%, 6%, 8% or 10%, etc.
[0052] In some embodiments, the mass percentage of the core material in the solid-liquid composite microcapsule is 40% to 60%. It can be understood that controlling the mass percentage of the core material in the solid-liquid composite microcapsule can further improve the lubrication performance of the solid-liquid composite microcapsule. When the mass percentage of the core material in the solid-liquid composite microcapsule is too high, the shell material may not be able to completely wrap the core material; when the mass percentage is too low, the lubrication performance of the solid-liquid composite microcapsule is poor. The mass percentage of the core material in the solid-liquid composite microcapsule can be, for example, 40%, 45%, 50%, 55% or 60%, etc.
[0053] Another embodiment of the present application provides a method for preparing the above-mentioned solid-liquid composite microcapsules, which preparation method includes one or more of an in-situ polymerization method, an interfacial polymerization method and a solvent evaporation method.
[0054] In some embodiments, the in situ polymerization method comprises the following steps:
[0055] The two-dimensional material, the dispersant and the lubricant are mixed to prepare a core material;
[0056] The core material is emulsified into micro-oil droplets in an aqueous phase containing a surfactant and a first shell material raw material, and the first shell material raw material is polymerized on the surface of the micro-oil droplets to form a shell material.
[0057] It should be noted that the present application has no particular restriction on the amount of surfactant used in the in-situ polymerization method, as long as the in-situ polymerization method can be used to prepare solid-liquid composite microcapsules.
[0058] In some specific embodiments, the first shell material raw material includes at least two of urea, formaldehyde, polyisocyanate and unsaturated polyol.
[0059] In some embodiments, the interfacial polymerization method comprises the following steps:
[0060] The two-dimensional material, the dispersant and the lubricant are mixed to prepare a core material;
[0061] After the initiator and the core material are mixed, the core material is emulsified into oil droplets in an aqueous phase containing a surfactant and a second shell material raw material, and the second shell material raw material is polymerized under the action of the initiator to form a shell material.
[0062] It should be noted that the present application has no particular restrictions on the amount of initiator and surfactant used in the interfacial polymerization method, as long as the interfacial polymerization method can be used to prepare solid-liquid composite microcapsules.
[0063] In some specific embodiments, the initiator includes one or more of azobisisobutyl cyanide, potassium persulfate, benzoyl peroxide, and azobisisoheptyl cyanide.
[0064] In some specific embodiments, the second shell material comprises one or more of methyl methacrylate, styrene and methyl styrene.
[0065] In some embodiments, the solvent evaporation method comprises the following steps:
[0066] The two-dimensional material, the dispersant and the lubricant are mixed to prepare a core material;
[0067] Dissolving the core material and the third shell material raw material in an organic solvent to obtain a mixed solution;
[0068] dispersing the mixed solution into an aqueous phase containing a surfactant for emulsification;
[0069] The emulsified liquid obtained by emulsification is heated to volatilize the organic solvent, and the third shell material raw material is precipitated to form the shell material.
[0070] It should be noted that the present application has no particular restrictions on the amount of organic solvent and surfactant used in the solvent evaporation method, as long as the solvent evaporation method can be used to prepare solid-liquid composite microcapsules.
[0071] In some specific embodiments, the organic solvent includes one or more of dichloromethane, dimethylformamide and chloroform.
[0072] In some specific embodiments, the third shell material includes one or more of polyimide, polystyrene, polymethyl methacrylate and polysulfone.
[0073] In some specific embodiments, the surfactant includes one or more of polyvinyl alcohol and gum arabic.
[0074] Another embodiment of the present application provides an application of the solid-liquid composite microcapsule or the solid-liquid composite microcapsule prepared by the above preparation method in preparing lubricating materials. The solid-liquid composite microcapsule can be used as a lubricating filler and compounded with a polymer matrix material to prepare a lubricating material for use.
[0075] The present application is further described in detail below in conjunction with specific examples and comparative examples. For experimental parameters not specified in the following specific examples, reference is given to the instructions given in the present application document, and reference may also be made to experimental manuals in the art or other experimental methods known in the art, or to experimental conditions recommended by manufacturers.
[0076] Example 1
[0077] The dispersant in this embodiment is polyisobutylene succinate, the two-dimensional material is molybdenum disulfide, the surfactant is polyvinyl alcohol, the shell material raw materials are urea and formaldehyde, the lubricant is PAO6 lubricating oil, and the curing agent is ammonium chloride and meta-diphenol.
[0078] A method for preparing a solid-liquid composite high-load microcapsule with a core material containing 15% molybdenum disulfide, comprising the following steps:
[0079] (1) 2% polyisobutylene succinate was dispersed in PAO6 lubricating oil (i.e., the mass percentage of polyisobutylene succinate to the mass percentage of PAO6 lubricating oil was 2%), and magnetic stirring was performed for 30 min. Subsequently, 15% molybdenum disulfide (i.e., the mass ratio of molybdenum disulfide to PAO6 lubricating oil was 0.15:1) was added, and magnetic stirring was performed for 30 min.
[0080] (2) In a 1L three-necked flask equipped with a stirring paddle, add 200mL of a 1wt% polyvinyl alcohol aqueous solution, 5g of urea, 0.5g of ammonium chloride and 0.5g of m-diphenol, stir until dissolved, and adjust the pH to 3.5 with hydrochloric acid;
[0081] (3) adding 10 g of the oil phase containing molybdenum disulfide obtained in step (1) into a three-necked flask and stirring and emulsifying for 10 min;
[0082] (4) adding 37% formaldehyde aqueous solution at a molar ratio of urea to formaldehyde of 1.5:1, reacting at 75°C for 4 hours, and then filtering to obtain solid-liquid composite microcapsules containing 15% molybdenum disulfide, wherein the shell material is urea-formaldehyde resin, and the mass percentage of the shell material in the solid-liquid composite microcapsules containing 15% molybdenum disulfide is about 40%.
[0083] The microcapsule composite material (solid-liquid composite microcapsule) of this embodiment was observed by scanning electron microscope and transmission electron microscope. Figure 2-3 As shown. Figure 2-3 It can be seen that the microcapsule composite material prepared in this application is a spherical structure, and the prepared microcapsule composite material successfully encapsulates molybdenum disulfide inside the shell material. The microcapsule composite material of this embodiment is subjected to a load test, and the results are as follows: Figure 4 As shown. Stainless steel is used as the friction pair, at 127mm 2 Under the conditions of contact area and 0.5kN-7kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment reaches 6kN.
[0084] Example 2
[0085] In this embodiment, the dispersant is benzylamine, the two-dimensional material is graphene, the surfactant is gum arabic, the initiator is azobisisobutyl cyanide, the shell material raw material is methyl methacrylate, and the lubricant is PAO6 lubricating oil.
[0086] A method for preparing a solid-liquid composite high-load microcapsule with a core material containing 10% graphene, comprising the following steps:
[0087] (1) 4% benzylamine was dispersed in PAO6 lubricating oil (i.e., the mass percentage of benzylamine to the mass percentage of PAO6 lubricating oil was 4%), and magnetic stirring was performed for 30 minutes. Then, 10% by mass of graphene (i.e., the mass ratio of graphene to PAO6 lubricating oil was 0.1:1) and azobisisobutyl cyanide were added, and magnetic stirring was performed for 30 minutes.
[0088] (2) In a 1 L three-necked flask equipped with a stirring paddle, add 200 mL of a 0.5 wt% aqueous solution of gum arabic;
[0089] (3) adding 10 g of the graphene-containing oil phase obtained in step (1) into a three-necked flask and stirring and emulsifying for 10 min;
[0090] (4) adding 5 g of methyl methacrylate monomer, reacting at 80° C. for 4 h, and then filtering to obtain solid-liquid composite microcapsules containing 10% graphene, wherein the shell material is polymethyl methacrylate, and the mass percentage of the shell material in the solid-liquid composite microcapsules containing 10% graphene is about 40%.
[0091] The microcapsule composite material of this embodiment was observed using scanning electron microscopy and transmission electron microscopy. Figure 2-3 The microcapsule composite material prepared in this application is similar to the spherical structure, and the prepared microcapsule composite material successfully encapsulates graphene inside the shell material. The microcapsule composite material of this embodiment is subjected to a load test, with stainless steel as the friction pair, at 127 mm 2 Under the conditions of contact area and 0.5 kN-7 kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment is about 6 kN.
[0092] Example 3
[0093] In this embodiment, the dispersant is Tween 80, the two-dimensional material is boron nitride, the surfactant is sodium dodecyl sulfate, the shell material is polyimide, and the lubricant is PAO6 lubricating oil.
[0094] A method for preparing a solid-liquid composite high-load microcapsule with a core material containing 20% boron nitride, comprising the following steps:
[0095] (1) 4% Tween 80 was dispersed in PAO6 (i.e., the mass percentage of Tween 80 to the mass percentage of PAO6 lubricant was 4%), and magnetic stirring was performed for 30 min. Subsequently, 20% by mass of boron nitride (i.e., the mass ratio of boron nitride to PAO6 lubricant was 0.2:1) was added, and magnetic stirring was performed for 30 min.
[0096] (2) In a 1 L three-necked flask equipped with a stirring paddle, add 200 mL of a 1 wt % aqueous solution of sodium dodecyl sulfate;
[0097] (3) dissolving 4 g of the oil phase containing boron nitride obtained in step (1) and 2 g of polyimide in 40 mL of dichloromethane, adding the mixture to a three-necked flask, and stirring and emulsifying for 10 min;
[0098] (4) After reacting at 45° C. for 4 hours, suction filtration was performed to obtain solid-liquid composite microcapsules containing 20% boron nitride, wherein the shell material was polyimide, and the mass percentage of the shell material in the solid-liquid composite microcapsules containing 20% boron nitride was about 60%.
[0099] The microcapsule composite material of this embodiment was observed using scanning electron microscopy and transmission electron microscopy. Figure 2-3 The microcapsule composite material prepared in this application is similar to the spherical structure, and the prepared microcapsule composite material successfully encapsulates boron nitride inside the shell material. The microcapsule composite material of this embodiment is subjected to a load test, with stainless steel as the friction pair, at 127 mm 2 Under the conditions of contact area and 0.5 kN-7 kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment is about 6 kN.
[0100] Example 4
[0101] The method is basically the same as Example 1, except that: in step (1), 1% by mass of molybdenum disulfide is added, that is, the mass ratio of molybdenum disulfide to PAO6 lubricating oil is 0.01:1.
[0102] The microcapsule composite material of this embodiment was subjected to a load test, with stainless steel as the friction pair. 2 Under the conditions of contact area and 0.5 kN-7 kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment is 3 kN.
[0103] Example 5
[0104] The method is basically the same as Example 1, except that: in step (1), 25% by mass of molybdenum disulfide is added, that is, the mass ratio of molybdenum disulfide to PAO6 lubricating oil is 0.25:1.
[0105] The microcapsule composite material of this embodiment was subjected to a load test, with stainless steel as the friction pair. 2 Under the conditions of contact area and 0.5 kN-7 kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment is 3 kN.
[0106] Example 6
[0107] The method is basically the same as Example 1, except that: in step (1), 30% by mass of molybdenum disulfide is added, that is, the mass ratio of molybdenum disulfide to PAO6 lubricating oil is 0.3:1.
[0108] The microcapsule composite material of this embodiment was subjected to a load test, with stainless steel as the friction pair. 2 Under the conditions of contact area and 0.5 kN-7 kN incremental load, the bearing capacity of the microcapsule composite material of this embodiment is 2 kN.
[0109] Comparative Example 1
[0110] Solid-liquid composite microcapsules were prepared by solvent evaporation method, the steps are as follows:
[0111] (1) Dissolve 2 g of polyimide and 4 g of PAO6 in 40 mL of dichloromethane;
[0112] (2) dissolving 1 g of polyvinyl alcohol and 0.5 g of gum arabic in water to obtain an aqueous phase, stirring the aqueous phase, and slowly adding the oil phase obtained in step (1) to obtain a mixed solution;
[0113] (3) The mixed solution obtained in step (2) is stirred at 45° C. for 4 hours to prepare polyimide microcapsules containing PAO6 oil, that is, the core material of the microcapsules is PAO6 lubricating oil, and the shell material is polyimide.
[0114] The microcapsule composite material of the comparative example was subjected to a load-bearing test, and the results are as follows: Figure 5 As shown. Stainless steel is used as the friction pair, at 127mm 2 Under the conditions of contact area and 0.5 kN-1.5 kN increasing load, the load-bearing capacity of the microcapsule composite material of this comparative example is only 1.5 kN, indicating that the lubrication performance of the microcapsule composite material prepared in comparative example 1 under high load is significantly worse than that of embodiments 1-6.
[0115] Comparative Example 2
[0116] The process is basically the same as Example 1, except that molybdenum disulfide is not added in step (1).
[0117] The microcapsule composite material of the comparative example was subjected to a load-bearing test, and the results were similar to those of Figure 5 Similar. With stainless steel as the friction pair, at 127mm 2 Under the conditions of contact area and 0.5kN-1.5kN increasing load, the load-bearing capacity of the microcapsule composite material of this comparative example is only about 1.5kN, which is obviously worse than the load-bearing capacity of the microcapsule composite material prepared in Example 1. This shows that the use of two-dimensional material and lubricant as core material can improve the high load-bearing capacity of the microcapsule composite material.
[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0119] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be noted that, for a person of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present application, and these all fall within the scope of protection of the present application. Therefore, the scope of protection of the patent application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A solid-liquid composite microcapsule, characterized in that: It comprises a core material and a shell material covering the core material, wherein the core material comprises a lubricant, a two-dimensional material and a dispersant, and the two-dimensional material comprises one or more of graphene, molybdenum disulfide, tungsten disulfide, boron nitride and black phosphorus; The lubricant comprises one or more of polyalphaolefin, perfluoropolyether, silicone oil and tung oil; The mass ratio of the two-dimensional material to the lubricant is (0.01-0.25): 1; The dispersant includes one or more of Tween 80, boronated polyisobutylene bissuccinimide, polyisobutylene succinate, benzylamine and ashless phosphate; The shell material includes one or more of urea-formaldehyde resin, polyimide, polystyrene, polyurethane and polysulfone; Based on the lubricant, the mass percentage of the dispersant to the lubricant is 0.1% to 10%; The mass percentage of the core material in the solid-liquid composite microcapsule is 40% to 60%.
2. The solid-liquid composite microcapsule according to claim 1, characterized in that: The mass ratio of the two-dimensional material to the lubricant is (0.1~0.2):
1.
3. The method for preparing the solid-liquid composite microcapsule according to claim 1 or 2, characterized in that: The preparation method comprises one or more of an in-situ polymerization method, an interfacial polymerization method and a solvent evaporation method.
4. The preparation method according to claim 3, characterized in that: The in-situ polymerization method comprises the following steps: Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material; The core material is emulsified into micro-oil droplets in an aqueous phase containing a surfactant and a first shell material raw material, and the first shell material raw material is polymerized on the surface of the micro-oil droplets to form the shell material; The first shell material raw materials include at least two of urea, formaldehyde, polyisocyanate and unsaturated polyol.
5. The preparation method according to claim 3, characterized in that: The interfacial polymerization method comprises the following steps: Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material; After mixing the initiator and the core material, the core material is emulsified into oil droplets in an aqueous phase containing a surfactant and a second shell material raw material, and the second shell material raw material is polymerized under the action of the initiator to form the shell material; The initiator includes one or more of azobisisobutyl cyanide, potassium persulfate, benzoyl peroxide and azobisisoheptyl cyanide; The second shell material raw material includes one or more of methyl methacrylate, styrene and methyl styrene.
6. The preparation method according to claim 3, characterized in that: The solvent evaporation method comprises the following steps: Mixing the two-dimensional material, the dispersant and the lubricant to prepare the core material; Dissolving the core material and the third shell material raw material in an organic solvent to obtain a mixed solution; dispersing the mixed solution into an aqueous phase containing a surfactant for emulsification; heating the emulsified liquid to volatilize the organic solvent and precipitate the third shell material raw material to form the shell material; The organic solvent includes one or more of dichloromethane, dimethylformamide and chloroform; The third shell material comprises one or more of polyimide, polystyrene, polymethyl methacrylate and polysulfone.
7. Use of the solid-liquid composite microcapsule according to claim 1 or 2 or the solid-liquid composite microcapsule prepared by the preparation method according to any one of claims 3 to 6 in the preparation of lubricating materials.
